2012
DOI: 10.1021/jo302368y
|View full text |Cite
|
Sign up to set email alerts
|

Chirality-Driven Folding of Short β-Lactam Pseudopeptides

Abstract: Novel enantiopure pseudopeptide models containing a central -(-lactam)-(Aa)-scaffold characterized by the combined presence of an -alkyl--amino--lactam (i+1) residue and a -substituted (i + 2) amino acid have been readily synthesized from -alkyl serines. The conformational analysis of such -lactam pseudopeptides conducted in CDCl3 and DMSO-d6 solutions using 1D-and 2D-NMR techniques revealed an equilibrium between -II turn and -turn conformers, which was ultimately modulated by the relative configuration of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…It can be expected that substitution of Phe 3 with other amino acids could modify the stability and geometry of the folded conformation 8a. 11c It was shown that peptides incorporating a central lactam‐Gly pair can exhibit high conformational heterogeneity around the lactamGly bond, depending on the presence and relative disposition of the substituents of the lactam scaffold 8a. 11b…”
Section: Resultsmentioning
confidence: 99%
“…It can be expected that substitution of Phe 3 with other amino acids could modify the stability and geometry of the folded conformation 8a. 11c It was shown that peptides incorporating a central lactam‐Gly pair can exhibit high conformational heterogeneity around the lactamGly bond, depending on the presence and relative disposition of the substituents of the lactam scaffold 8a. 11b…”
Section: Resultsmentioning
confidence: 99%
“…Later on, other studies showed that this neuropeptide is able to alleviate the behavioral changes caused by PD in animal models. , Given the therapeutic potential of MIF-1 in neurodegenerative processes, its bioactive conformation was investigated. X-ray crystallography and structure–activity relationship studies using constrained peptidomimetics suggest that MIF-1 adopts a type-II β-turn formed by intramolecular hydrogen bonding between the carbonyl oxygen atom of the l -proline residue and the trans amide proton of the glycinamide residue (depicted as dashed blue lines in Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…While 6a is expected to adopt preferentially a classical γ-turn conformation, the existence of other turn motifs (including the postulated type II β-turn) or extended conformations cannot be ruled out due to its high flexibility. In fact, Aizpurua and co-workers disclosed MIF-1 peptidomimetics containing a β-lactam as a l -leucine surrogate in equilibrium between type II β-turn and γ-turn conformations …”
Section: Resultsmentioning
confidence: 99%
“…In fact, Aizpurua and coworkers disclosed MIF-1 peptidomimetics containing a βlactam as a L-leucine surrogate in equilibrium between type II β-turn and γ-turn conformations. 19 Moreover, using conformationally rigid peptidomimetics containing indolizidinone and spirobicyclic scaffolds, Johnson's lab has shown that other β-turn conformations such as VI βturn may be able to accommodate key pharmacophores in the same topological space. 2 However, in the case of 4a, β-turn conformations are excluded since the C-terminal carboxamide is absent (cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation